ANALISIS PERBUATAN CATCALLING JIKA DILIHAT DARI SUDUT PANDANG HUKUM PIDANA - Griyani Elisabeth Purba; Nike Margaretha Br Sembiring; Santiana Siboro; Reh Bungana Br Perangin Angin (ADISAM PUBLISHER, 2023)
Harassment is an unwanted verbal or behavioral act in which someone shouts or calls someone's attention with inappropriate or sexually harassing words or comments in a public place. In criminal law, intimidation can take the form of verbal expression or violence. However, the legal status of subpoenas varies by country. Generally, criminal law covers various forms of disclosure, including verbal disclosure. Some countries or regions have laws or regulations that specifically cover sales offers. Police usually rely on available evidence and witnesses. Depending on the seriousness of the crime and local customs, penalties can also range from fines to prison terms. It is important to remember that solicitation laws and regulations may change over time and vary from one confirmation to another. Therefore, it is important for individuals to understand local laws and notify the authorities if they are victimized. If you or someone you know is the victim of a phone call, the general recommendation is to contact a local attorney or law firm for appropriate legal advice based on the situation and specifically on sexual disclosure.